1994
DOI: 10.1117/12.175102
|View full text |Cite
|
Sign up to set email alerts
|

<title>Dual-energy computed radiography: improvements in processing</title>

Abstract: We have reported on a single-exposure dual-energy system based on computed radiography (CR) technology. In a clinical study conducted over a two year period, the dual-energy system proved to be highly successful in improving the detection (p=0.0005) and characterization (p=0.005) of pulmonary nodules when compared to conventional screen-film radiography. The basic components of our dual-energy detector system include source filtration with gadolinium to produce a bi-modal x-ray spectrum and a cassette containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The framework employed above provides a description of DE imaging performance accounting not only for quantum and electronic noise as factors for system optimization but also anatomical noise and imaging task. Other factors that warrant consideration are part of future work that incorporates scatter 26,[52][53][54][55] and noise reduction algorithms [56][57][58] in description of the DQE and NEQ. Such noise reduction algorithms include filtering of the high-energy imaging, correlated noise reduction, and noise clipping-outside the scope of the present analysis but certainly within the scope of this framework and an important consideration in assessing the full potential of DE imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The framework employed above provides a description of DE imaging performance accounting not only for quantum and electronic noise as factors for system optimization but also anatomical noise and imaging task. Other factors that warrant consideration are part of future work that incorporates scatter 26,[52][53][54][55] and noise reduction algorithms [56][57][58] in description of the DQE and NEQ. Such noise reduction algorithms include filtering of the high-energy imaging, correlated noise reduction, and noise clipping-outside the scope of the present analysis but certainly within the scope of this framework and an important consideration in assessing the full potential of DE imaging.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,31 Several other methods were also introduced, focusing on improving the sharpness and noise texture, including noise forcing ͑NOF͒ and noise clipping ͑NOC͒ developed in our laboratory. 27,29 Three model-based algorithms are described below and were compared for noise reduction efficacy to a simple smoothing filter ͑SSF͒ consisting of a rotationally symmetric Gaussian filter to smooth the high-energy image. The Gaussian function was implemented in Matlab ͑Mathworks, Natick, MA͒ with a ROI size of 19 pixels and a FWHM of 4.71 pixels.…”
Section: Noise Reduction Algorithmsmentioning
confidence: 99%
“…A regionally optimized nonadaptive form of correlated noise reduction, as described by Kalendar, 24 McCullough, 25 and Ergun. 26,29 was implemented. Kalendar demonstrated that noise in the reconstructed bone and tissue images was anticorrelated.…”
Section: Kalender's Correlated Noise Reduction (Kcnr)mentioning
confidence: 99%
See 1 more Smart Citation
“…[40,214,74,45]), or on dual energy systems in chest radiography (e.g. [107,67,90]) is beyond the scope of this review as are studies that use psychophysics, e.g. to determine the optimum tube voltage [10] or to aid the detection of abnormalities by measuring visual dwell [106,144].…”
Section: Chapter 2 Computer Analysis Of Chest Radiographs -A Reviewmentioning
confidence: 99%